2021
DOI: 10.3389/fimmu.2021.623762
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Classifier Reveals Prognostic Osteosarcoma Microenvironment Molecular Subtypes

Abstract: Osteosarcoma (OSA) is the most common bone malignancy and displays high heterogeneity of molecular phenotypes. This study aimed to characterize the molecular features of OSA by developing a classification system based on the gene expression profile of the tumor microenvironment. Integrative analysis was performed using specimens and clinical information for OSA patients from the TARGET program. Using a matrix factorization method, we identified two molecular subtypes significantly associated with prognosis, S1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…CAFs or cancer associated fibroblasts represent a major population in the TME of many solid tumours, however their origin and role in tumour progression is complex and they can generate pro-tumourigenic and anti-tumourigenic secretory factors. Phenotypically and functionally different CAF subtypes based on cell-surface markers such as podoplanin (PDPN), a-smooth muscle actin (aSMA), fibroblastactivated protein (FAP), fibroblast-specific protein-1 (FSP-1/ S100A4), THY1 (also known as CD90), and platelet-derived growth factor receptor-a, and b (PDGFRa and PDGFRb) have been associated with different tumour types, stages and patient survival (107)(108)(109)(110)(111). Recently, the ability of CAFs to modulate the immune responses has been discovered and is being explored to improve cancer therapies.…”
Section: Tme Factors Affecting DC Development In Tumours Pro-and Anti...mentioning
confidence: 99%
“…CAFs or cancer associated fibroblasts represent a major population in the TME of many solid tumours, however their origin and role in tumour progression is complex and they can generate pro-tumourigenic and anti-tumourigenic secretory factors. Phenotypically and functionally different CAF subtypes based on cell-surface markers such as podoplanin (PDPN), a-smooth muscle actin (aSMA), fibroblastactivated protein (FAP), fibroblast-specific protein-1 (FSP-1/ S100A4), THY1 (also known as CD90), and platelet-derived growth factor receptor-a, and b (PDGFRa and PDGFRb) have been associated with different tumour types, stages and patient survival (107)(108)(109)(110)(111). Recently, the ability of CAFs to modulate the immune responses has been discovered and is being explored to improve cancer therapies.…”
Section: Tme Factors Affecting DC Development In Tumours Pro-and Anti...mentioning
confidence: 99%
“…Unlike epithelial cancers, the current understanding of the origin and contribution of CAFs in sarcomas is very limited. Studies in Ewing sarcoma 144 and osteosarcoma 145 have demonstrated that extracellular vesicles and associated cargo secreted from tumor cells drive the transformation of normal fibroblasts into CAFs. On the contrary, rhabdomyosarcoma cells do not rely on CAFs to prime the ECM for local tumor expansion, but rather produce their own ECM with minimal involvement of CAFs 146 .…”
Section: Barriers To Immunotherapy For Soft Tissue and Bone Sarcomamentioning
confidence: 99%
“…Our knowledge remains sparse for other types of solid malignancies of non-epithelial origin, e.g., in sarcomas. Except for Ewing sarcoma [42] and osteosarcoma [43], the role of CAFs in sarcomas of different origins is unclear. Further, CAFs have not been extensively studied in haematological malignancies so far.…”
Section: Fibroblasts As a Fundamental Bioactive Part Of The Majority ...mentioning
confidence: 99%